ENVIRONMENTAL IMPACT OF IDOL IMMERSION ON KAKERPURA LAKE MHOW - Billore, D.K.; Dandawate, Maneesha (International Journal of Research -GRANTHAALAYAH, 2015)
This paper intends to prepare the environmental impact of "Ganesh Idol" & "DurgaPratima" immersion on water quality of Kakerpura Lake, Mhow. For this purpose site of Kakerpura lake was selected where idols are actually immersed. Water samples were collected in morning at different intervals i.e. pre-immersion (August) immersion (September, October) Post immersion period (November). The "Ganesh Idols" & "DurgaPratima" are made up of degradable and non-degradable components and paints containing heavy metals due to that immersion activity deteriorates water quality. The physico-chemical parameters were analysed to study the environmental impact of idol immersion on Kakerpura Lake and these parameters shows the significant variation due to immersion of idols.